Study Synthesis of Sonlt'Vitamine - C Drivatives (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The present Work include the nove] s)ihesis of 2,3-j!-isopropytidene vitamin-c, from the reaction of dry acetone with 'Vitamin-c in excess of acetyictJoride ,the reaction completed afeter(48) hi . and shows a four products 2,3 -JL-Isopropylidene, 5 , 6Q.. -Isopropylidene and2.3 -O-diacetryI and 3-0 -acetyl vitamin-c.These four products were separted bv uisne: column chromantotograhytyPe (srncagel chromatography